2018
DOI: 10.1103/physrevb.97.201104
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of strain-induced orbital valence band splitting in HfSe2 by sodium intercalation

Abstract: By using angle-resolved photoemission spectroscopy (ARPES), the variation of the electronic structure of HfSe2 has been studied as a function of sodium intercalation. We observe how this drives a band splitting of the p-orbital valence bands and a simultaneous reduction of the indirect band gap by values of up to 400 and 280 meV respectively. Our calculations indicate that such behaviour is driven by the band deformation potential, which is a result of our observed anisotropic strain induced by sodium intercal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
3
5
1
Order By: Relevance
“…A recurrent question in the study of alkali-metal dosed surfaces of 2D materials is whether the dosed atoms remain on the surface and set up a vertical electric field, or intercalate into the sample [1][2][3][4][6][7][8][9][10][11][12][13][38][39][40][41][42]. A number of recent studies on TMDCs and similar materials have claimed that the alkali metal atoms remain on the surface [2][3][4][5][6]8,9,42], in the case that the sample remains at low temperatures throughout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recurrent question in the study of alkali-metal dosed surfaces of 2D materials is whether the dosed atoms remain on the surface and set up a vertical electric field, or intercalate into the sample [1][2][3][4][6][7][8][9][10][11][12][13][38][39][40][41][42]. A number of recent studies on TMDCs and similar materials have claimed that the alkali metal atoms remain on the surface [2][3][4][5][6]8,9,42], in the case that the sample remains at low temperatures throughout.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative scenario is intercalation, in which the K atoms migrate into the van der Waals gap between layers, leading to an increased van der Waals gap that causes decoupling of the topmost layer both structurally and electronically. This scenario is known to occur almost immediately at room temperature [1] but is also often applied to dosing studies of TMDCs even when the sample is held at low temperatures [7,10,40]. This topmost layer also becomes doped due to the donated electrons from the K + ions.…”
Section: Resultsmentioning
confidence: 99%
“… 35 Since the charge density wave transition temperature of HfSe 2 is rather low, we can exclude this interpretation here. It has been shown that HfSe 2 is a suitable host material for extrinsic dopant atoms, 36 suggesting that the bright defects might be a result of the intercalation of impurities.…”
Section: Resultsmentioning
confidence: 99%
“…But also resistivity [40,[47][48][49], conductivity [3,43] Hall coefficient, [47], magnetic susceptibility [3], scanning transmission electron microscopy [39], and electron energy-loss [50,51] experiments were performed. The investigations were supported by numerous theoretical approaches [11,14,27,31,38,43,[52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 97%
“…Besides transition metals [60][61][62], which have been intercalated into both materials, alkali metals have been used as electron donors for HfSe 2 [63,64]. Lithium [65,66] and sodium [6,56] doping leads to a transition from semiconducting to metallic behavior. In the pristine materials, the valence states are mainly comprised of S/Se p-orbitals which are almost filled due to a transfer of electrons from the hafnium atoms [67].…”
Section: Introductionmentioning
confidence: 99%